OP0002 Use of anti-TNF therapy is associated with reduced cardiovascular event risk in rheumatoid arthritis. (23rd January 2014) - Nurmohamed, M.T.; Bao, Y.; Signorovitch, J.; Mulani, P.M.; Furst, D.E.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased risks for cardiovascular (CV) comorbidities because of an increased prevalence of traditional CV risk factors and the underlying chronic inflammatory process. Objectives: To assess the effects of treatment with anti–tumor necrosis factor (anti-TNF) therapy, methotrexate (MTX), or other nonbiologic DMARDs on CV event risk in patients with RA. Methods: Adult patients with ≥2 RA diagnoses (ICD-9 CM: 714.xx) and ≥1 filled prescription of anti-TNF therapy, MTX, or other nonbiologic DMARD were identified in the Thomson Reuters MarketScan® database (2003–2010). Patients were assessed from index fill date to first inpatient CV diagnosis of myocardial infarction (MI), stroke, unstable angina, or heart failure (HF) to the end of health plan enrollment or to 6 months after the discontinuation of their index drug, whichever came first. Cox proportional-hazards models assessed the effect of cumulative exposure to anti-TNF therapy, MTX, and other nonbiologic DMARDs on occurrence of CV events. We adjusted for baseline (ie, 1 year before index prescription) demographics; use of therapies for RA (eg, MTX, corticosteroid), CV-related medications, and smoking deterrents; comorbidities (eg, dyslipidemia, hypertension, diabetes); history of CV events; and medical resource use. Subgroup and sensitivity analyses also were conducted. Results: The study identified 109, 462 patients with 105, 920 total patient-years (PYs) of follow-up, including 48, 621 PYs of exposure to anti-TNF therapies (31, 466 as monotherapy), 35, 480 PYs of exposure to MTX (18, 325 as monotherapy) and 52, 994 PYs of exposure to other nonbiologic DMARDs (9, 441 as monotherapy). A total of 1743 patients (1.6%) had a CV event after their index prescription. In the multivariate regression model, each additional 6 months of anti-TNF therapy significantly reduced the risk for any study CV event (hazard ratio [HR]=0.87, 95% confidence interval [CI]=0.80–0.96, P =.005) and for MI (HR=0.80, CI=0.67–0.95, P =.013), compared with patients without anti-TNF biologics, after adjusting for cumulative exposure to MTX or other nonbiologic DMARD. The effects of cumulative use of MTX and other nonbiologic DMARDs were not statistically significant. In the subgroup analyses, each additional 6 months of anti-TNF therapy use was significantly associated with a reduction in CV events in patients aged ≥50 years (HR=0.86, CI=0.77–0.96, P =.007) as well as in those without prior MTX use (HR=0.85, CI=0.73–0.98, P =.022). In the full sample, the multivariate regression model predicted that cumulative use of anti-TNF therapy for 1, 2, or 3 years would reduce CV event risks by 24%, 42%, and 56%, respectively, compared to not using anti-TNF therapies during those time periods, adjusting for background use of MTX or other nonbiologic DMARDs. Conclusions: Use of anti-TNF therapies vs. non-use was associated with significantly lower risks for CV events (ie, inpatient diagnoses for MI, stroke, unstable angina, or HF) in patients with RA, older patients with RA, and patients without prior exposure to MTX, adjusting for use of MTX and other nonbiologic DMARDs. Disclosure of Interest: M. Nurmohamed Grant/Research support from: Abbott, Consultant for: Abbott, Speakers Bureau: Abbott, Y. Bao Shareholder of: Abbott, Employee of: Abbott, J. Signorovitch Consultant for: Abbott (Analysis Group is under contract with Abbott), Employee of: Analysis Group, P. Mulani Shareholder of: Abbott, Employee of: Abbott, D. Furst Grant/Research support from: Abbott, Consultant for: Abbott, Speakers Bureau: Abbott